Welding Inspection Technology (Ametican Welding Society, 2008)
This publication deals broadly with Welding Inspection Technology and Certification. the welding inspector must have a wide range of knowledge and skills, because it involves more than simply looking at welds. Consequently, this course is specifically designed to provide both experienced and novice welding inspectors a basic background in the more critical job aspects